A SET route to Ethyl Carboxylic Acid from Ethanol and Carbon Monoxide - Ragnar Larsson (Open Journal of Chemistry - Peertechz Publications, 2020)
As a hypothetical experiment the reaction between carbon monoxide and ethanol to form an ethyl carboxylic acid has been considered. The SET model for catalysis is used. The effect of the catalyst COS on the reactivity of these two species is found to lead to the expected result.